The Secret History of the Jersey Devil : How Quakers, Hucksters, and Benjamin Franklin Created a Monster - Regal, Brian; Esposito, Frank J. (Book collections on Project MUSE., 2018)
"A fascinating and scholarly examination of the origins of the Jersey Devil, a mythical beast born in the colonial era and which lives on to this day. Written in a style suitable for general readers. Good regional trade and course adoption potential. Really interesting. Heavily researched and written in a lively narrative, The Secret History explodes the many myths surrounding the Jersey Devil. Provocative and entertaining and unlike any book written before on the subject, it finds the origins of New Jersey's favorite monster not in the realm of the occult, but in the bare-knuckled political and religious upheavals and fights of colonial America. The real story of the Jersey Devil's birth is far more interesting, complex, and important than anyone thinks. It is a product not of witchcraft, but innuendo, scandal, rumor mongering, and media hype. While a tale of early America, it could have been taken from the tabloids and internet gossip of today"--